Análisis de los factores que influyen en la fidelidad del consumidor de la ciudad de Loja, caso de estudio La Sureñita. - Macas Ramirez., Ambar Dayana (2024)
The objective of this work of curricular integration is to analyze the factors that influence consumer loyalty in Loja city, taking as a case study the company "La Sureñita". The methodology used was based on the deductive method, with a descriptive quantitative approach. A simple random sampling was carried out, covering a total of 436 individuals, comprising 382 families residing in Loja city, 53 retail clients and the manager of the company "La Sureñita". The methodology used was based on the deductive method, with a descriptive quantitative approach. A simple random sampling was carried out with a total of 436 individuals, comprising 382 families living in the city of Loja, 53 retail customers and the manager of the company "La Sureñita". Tools such as surveys and questionnaires were used to collect information. The results obtained revealed that 95% of consumers in the city of Loja directly link product quality with their loyalty to the "product quality" factor. Regarding the "perceived value" factor, 77% stated that it does influence their level of satisfaction. Regarding the "customer satisfaction" factor, 87% of consumers associated satisfaction with loyalty. The influence of the "customer experience" factor on loyalty was 77%. For the "trust and credibility" factor, a weight of 84% was observed. In last place, the factor "loyalty programs" showed less influence, with 76%; nevertheless, 94% of consumers support the implementation of such programs. It should be noted that the most relevant factors for consumers are product quality and customer satisfaction. In other words, satisfying the consumer and offering quality products are fundamental aspects for achieving significant success in consumer loyalty